Alignment everywhere all at once: Applying the late aggregation principle to a typological database of argument marking - Inman, David; Witzlack-Makarevich, Alena; Chousou-Polydouri, Natalia; Steiger, Melvin (Journal of Language Modelling, 2024)
This article presents the structure of the ATLAs Alignment Module, a typological database designed to exhaustively capture languageinternal variation in argument marking (indexing and flagging). The flexible design of our database can be extended to cover further aspects of morphosyntactic alignment. We demonstrate with a small diversity sample how the database can be queried and the data aggregated at different levels of structure (e.g. for a language as a whole or for individual referential types in the form of alignment statements) for the purposes of cross-linguistic comparison. The database is made available in the Cross-Linguistic Data Formats (CLDF), and we provide code that generates an array of aggregations.